Analysing The Problems Faced by The Students at The Sixth Semester to Speak English at English Education Department - Raqib, Muhammad; Firman; Sastrawati, Ika (FKIP Unismuh Makassar, 2023)
This study aimed to find out the problems faced by the students in the sixth semester of English Education Department at Unismh Makassar to speak English fluently in the class and the factors causing the problems. This study used descriptive qualitative method in type of phenomenology in which the researcher used observation checklist and semi-structure interview to collect the data. The results showed that there are two main problems faced by the students to speak English fluently, namely linguistic problems which consist of: poor in grammar, lack of vocabulary and lack of pronunciation and also non-linguistic problems which consist of: blankness, shyness and anxiety. The factors causing students are poor in grammar manly caused by: seldom to learn grammar by themselves and were seldom to learn grammar in the previous semesters. Lack of vocabulary is caused by the students are not motivated to improve vocabulary by themselves. Lack of pronunciatiaon are caused by: the interference of mother tongue, lack of practice by themselves and pronunciation classes lacked of practice. In addition, blankness are mainly caused by: forget what to say, interruption and eye contact. Furthermore, shynes is caused by the students are afraid of making mistakes. Lastly, anxiety is caused by the students are afraid of being laughed or judged and commentated by the lectures if making mistakes.